2021
DOI: 10.1021/acsaelm.0c01052
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pH Tolerance in Conductive Al-Doped ZnO Nanofilms via Sequential Annealing

Abstract: Chemically stable and electrically conductive metal oxide nanofilms are promising as robust electrodes for chemical/ biosensors and for photoelectrochemical applications, which require harsh conditions (e.g., acidic or basic environments). Among the various conductive metal oxides, impurity-doped ZnO nanofilms deposited on substrates are chemically nonresistive to acidic and basic environments because of the inevitable etching effects. Herein, we demonstrate a strategy to enhance the pH tolerance of Al-doped Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Resistance increase was calculated as ( R – R 0 )/ R 0 , where R and R 0 are the resistance at 25 min immersion in each pH buffer solution and the initial resistance before the stability tests, respectively. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Robustness and Stability Of Properties Under Harsh Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance increase was calculated as ( R – R 0 )/ R 0 , where R and R 0 are the resistance at 25 min immersion in each pH buffer solution and the initial resistance before the stability tests, respectively. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Robustness and Stability Of Properties Under Harsh Environmentsmentioning
confidence: 99%
“…Yan et al reported that sequentially annealed AZO thin films (first annealed in air and then in a Zn vapor atmosphere) demonstrated superior pH tolerance in a wide pH range from 3 to 11 (Figure 10). 29 The etching rate of the sequentially annealed AZO thin films at pH 3 was 0.2 nm/min, whereas that of as-grown AZO thin films was 3.2 nm/min. It is noteworthy that the chemical stability of sequentially annealed AZO thin films at pH 3 is comparable to that of the singlecrystalline Zn-polar ZnO (0001) surface, which is known to be much more stable than O-polar ZnO (0001) in an acidic environment (Figure 9).…”
Section: Robustness and Stability Of Propertiesmentioning
confidence: 99%
See 1 more Smart Citation